IgG4-Related Hepatic Pseudotumor Masquerading as a Klatskin Tumor - Jennifer Yoon; Steve Hu; Daniel Phillips; Amir Fathi; Adnan Ameer (Case Reports in Hepatology)
Immunoglobulin G subclass 4 (IgG-4)-related disease (IgG4-RD) is an uncommon immune-mediated, fibro-inflammatory disease which has garnered recognition as a systemic condition. One manifestation of the disease in the hepatobiliary system is the development of hepatic inflammatory pseudotumors. These benign tumors are often misdiagnosed as malignant tumors and undergo unnecessary hepatic resections. We present a case of IgG4-related hepatic inflammatory pseudotumor (IPT) mimicking a Klatskin tumor. A high degree of clinical suspicion and extensive workup is imperative in reaching the correct diagnosis. IgG4-related inflammatory pseudotumor is a rare entity, but an important consideration in evaluating hepatic tumors.